Impact of Smart Services to Current Value Networks / Martin Rabe ...[et al.] - Rabe, Martin; Kühn, Arno; Dumitrescu, Roman; Mittag, Tobias; Schneider, Marcel; Gausemeier, Jürgen (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Promising market offerings are increasingly based on the close interaction of physical products and accompanying services – this is expresses by the term product service systems. A new trend is the expansion of the product service systems by data-driven, intelligent services (called Smart Service). Examples include predictive maintenance or automated re-ordering of consumables and materials. Such enhancements can significantly help to secure the customer interface and generate additional profitable business with new revenue models, such as pay-per-use rather than selling a machine. To take advantage of this opportunity, companies must develop promising Smart Services and implement them in their value network. The present paper shows the necessary steps for a company. The first step shows methods for the conception of Smart Services. The second step is the analysis of the current value networks. A comparison of the new functions and requirements of the Smart Services with the value network leads to effects and necessary changes. In the last step, changes are translated into a roadmap for implementation.